Analisis Nilai Pendidikan Karakter Dalam Film Kartun "Zootopia" - Putri Ayu Cempaka; Wikanengsih Wikanengsih; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study discusses the analysis of the value of character education contained in the film “Zootopia”. This research was conducted because of the many assumptions that the morale and character of the younger generation are damaged, which is marked by the proliferation of news in electronic media that presents deviant juvenile crime and delinquency. This involves children in their teens, children who are still in school, and other young generations. At present, there has been a decline in the interest of children and adolescents towards cartoon films, this certainly makes researchers think whether there are lessons and character education contained in the cartoon “Zootopia”? What makes researchers interested in the film “Zootopia” is that everyone has the right to have dreams that can be realized even though the circumstances around us are not supportive. The method used in this study is a note-taking method to collect data and the theory used to dissect this research is the sociological theory of literature which focuses on the value of character education in the film “Zootopia”. The results of the research carried out are that the cartoon film “Zootopia” contains character education values, this is reflected throughout the film show, such as honesty, nationalism, responsibility, discipline, courage, democracy, attitude of help and friendship.